UNDERSTANDING MATERIAL REMOVAL MECHANISM AND EFFECTS OF MACHINING PARAMETERS DURING EDM OF ZIRCONIA-TOUGHENED ALUMINA CERAMIC - Bilal, Azat; Perveen, Asma; Talamona, Didier; Pervej Jahan, Muhammad (micromachines, 2021)
Non-conductive structural ceramics are receiving ever-increasing attention due to their outstanding physical and mechanical properties and their critical applications in aerospace and biomedical industries. However, conventional mechanical machining seems infeasible for the machining of these superior ceramics due to their extreme brittleness and higher hardness. Electro discharge machining (EDM), well known for its machining of electrically conductive materials irrespective of materials hardness, has emerged as a potential machining technique due to its noncontact nature when complemented with an assistive electrode technique. This paper investigates the material removal mechanism and effects of machining parameters on machining speed and dimensional and profile accuracies of features machined on zirconia toughened alumina (ZTA) ceramics using assistive electrode EDM...
Keywords: ceramics; taper; thermal spalling